THIRD GENERATION LEARNING IN BUSINESS ENGLISH - Stepanova, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Third generation learning in Business English is a tool increasing students’ life-long competences and achievements. Business English today is about communication where the content and the communicative competences- linguistic, sociolinguistic and pragmatic are of crucial importance.  The article reflects the results of 3rd generation learning in Business English in post-secondary institution in Latvia where students using team-based learning in the classroom mastered their language skills and communicative competences to achieve an academic success.